Mechanism research on crack propagation in coal induced by CO2 phase-transition fracturing under different lateral compression coefficients. Issue 6 (November 2021) - Li, Qingsong; Fu, Jinlei; Heng, Xianwei; Xu, Xiaoqian; Ma, Shu
To study crack propagation around the fracture hole in the coal body induced by high-pressure CO2 gas produced by CO2 phase transition fracturing, the mechanism of permeability enhancement of fractured coal induced by liquid CO2 phase transition fracturing was studied from two aspects, the process of coal gas displacement by competitive adsorption and physical characteristics of fractured coal induced by phase transition. Crack propagation pattern in coal under different lateral coefficients was explored by using discrete-element numerical simulation software. Distribution characteristics of hoop stress of fractured coal were analyzed through theoretical calculation. The results show that: (1) Micro-cracks in damaged coal body generated during phase transition process are mainly crack_tension type, which are formed by the composite action of tension and compression. The crack propagation is the result of the continuous release of compressive stress from concentrated area to the surrounding units. Micro-cracks are radially distributed in a pattern of "flame". (2) The main crack formed above the fracture hole grows in the direction of vertical minimum initial stress, and the main crack formed below the fracture hole develops in the direction of horizontal initial stress. As the lateral compression coefficient increases, the extension distance of the second crack will not change after reducing to a certain length. (3) As the distance from the fracture hole increases, the peak compression loaded at the monitoring point decays, and the loop stress in the cracked coal is distributed in a pattern of "peanut". It provides practical methods and ideas for studying the macroscopic and microscopic development of cracks, as well as theoretical support for the on-site hole layout.